Motherpreneur Untuk Meningkatkan Ekonomi Keluarga Pada Kelompok Ibu Di Desa Demangan Kecamatan Karangdowo Kabupaten Klaten - Paramita Lea Christanti (Jurnal Abdimas Ekonomi dan Bisnis, 2022)
The current pandemic has led to a wave of layoffs in several sectors. Layoffs result in economic disruption in the family. Motherpreneurs can be an option in the midst of economic difficulties in the family. Motherpreneur can be interpreted as a housewife who can also be an entrepreneur. Housewives have many skills that can be explored and provided with provisions that can be used to open business opportunities. Provide training on several selling ideas in the culinary field and provide training on the use of social media and markerplaces as a means of product promotion. It is hoped that these mothers will become more economically independent and at the same time support the family economy. This community service is carried out in Demangan Village, Karangdowo District, Klaten Regency. Keyword : Pandemic, Layoffs, Economic Disruption